APLIKASI OCR (OPTICAL CHARACTER RECOGNITION) TULISAN TANGAN AKSARA BALI DENGAN METODE CONTOUR ANALYSIS - Dharma Laksana, I Kadek; Gede Sunarya, I Made; Mahendra Darmawiguna, I Gede (Universitas Pendidikan Ganesha, 2015)
The sophistication of computer development widely used in the processing application Optical Character Recognition (OCR). Optical Character Recognition (OCR) is a mechanical or electronic conversion of scanned images handwritten, typed, or printed text into encoded to computer. Studies on lately OCR provide a method with good accuracy and computational speed is getting lighter. The purpose development of application is for help user in doing translate handwritter aksara into latin.Â Implementation of this ocr aksara bali handwritten application uses the contour metode of EmguCV and OpenCV library as the supporter of image recognition process. Autocorellation and Intercorellation as detection of contour methodâ€™s fuction. This application is developed by using free software from Microsoft corporate that is Microsoft Visual C# 2010 Express (csharp). The design is done by using the functional form of UML (Unified Modeling Languange) modelsÂ The results of this study in the form of OCR-based desktop application which has been successfully developed. The entire functional requirements have been successfully implemented in accordance with the design. Tests on some samples there has also been successfully implemented as well.